(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Crime, repression and injustice have always been parts ofthe human society, so also the prisons. Traditionally prisons and prisonershave been considered as somewhat violative and frightful entities by thesocieties. The history of prison and its use as a place of detention for thecondemned persons is not of recent origin but is very old. The outlawed inmatesof a prison, till the beginning of the century, were never considered fit toclaim any right enjoyed by the law abiding citizens of the society. They wereput in jail only to realize their folly and to pay for it through theirsufferings.